2012
DOI: 10.1088/1674-4926/33/7/073001
|View full text |Cite
|
Sign up to set email alerts
|

Humidity sensing properties of Cu2O-PEPC nanocomposite films

Abstract: A blend of copper oxide nanopowder (Cu 2 O), 3 wt.%, and poly-N-epoxypropylcarbazole (PEPC), 2 wt.%, in benzol was drop-casted on glass substrates with pre-deposited surface-type silver electrodes for the fabrication of Cu 2 O-PEPC nanocomposite thin films. The thicknesses of the Cu 2 O-PEPC films were in the range of 10-13 m. The effect of humidity on the electrical properties of the nanocomposite films was investigated by measuring the capacitance and dissipation of the samples at two different frequencies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…The humidity sensing capability of a blend of Cu 2 O and PEPC has been investigated in our previous study and the bandwidth of the sensor was found to be 36-86% RH, whilst its sensitivity was found to be 0.83 pF/%RH [3]. The humidity sensing capability of NiPc has also been investigated earlier by Shah et al [1] who reported a nonlinear increase in capacitance value with increasing humidity level from 35% to 90% RH, while the sensitivity was reported to be 8.93 pF/%RH. Keeping in mind the potential of NiPc and PEPC for humidity sensors, we have investigated a film of organic-inorganic composite of PEPC, NiPC and Cu 2 O as humidity sensor, where Cu 2 O is used as template to enhance the surface roughness.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The humidity sensing capability of a blend of Cu 2 O and PEPC has been investigated in our previous study and the bandwidth of the sensor was found to be 36-86% RH, whilst its sensitivity was found to be 0.83 pF/%RH [3]. The humidity sensing capability of NiPc has also been investigated earlier by Shah et al [1] who reported a nonlinear increase in capacitance value with increasing humidity level from 35% to 90% RH, while the sensitivity was reported to be 8.93 pF/%RH. Keeping in mind the potential of NiPc and PEPC for humidity sensors, we have investigated a film of organic-inorganic composite of PEPC, NiPC and Cu 2 O as humidity sensor, where Cu 2 O is used as template to enhance the surface roughness.…”
Section: Introductionmentioning
confidence: 94%
“…These features give organic semiconductors an economic and technological edge over conventional inorganic semiconductor sensing materials. Consequently, extensive R&D efforts have been directed towards various organic semiconductors and their composites to identify appropriate materials for humidity sensing applications [1–5]. A good sensing material must meet certain stringent requirements such as high sensitivity, reproducibility, fast response and recovery time, small hysteresis, low power consumption and portability, along with durability and long lifetime [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karimov et al have reported on the characterization of humidity sensors based on copper oxide nanoparticles and poly‐ N ‐epoxypropylcarbazole (Cu 2 O–PEPC) nanocomposite films. They studied the capacitive and electrical dissipation responses of the Cu 2 O–PEPC hybrid system toward the change of RH and have performed under operating frequencies of 120 Hz and 1 kHz and under applied voltage.…”
Section: Organic Materials For Humidity Sensorsmentioning
confidence: 99%
“…b) Resistance–relative humidity (RH) relationships of the Ag/Cu 2 O–PEPC/Ag device measured at 1) DC, 2) 120 Hz, and 3) 1 kHz of the applied voltage. Reproduced with permission . Copyright 2012, IOP Publishing Ltd.…”
Section: Organic Materials For Humidity Sensorsmentioning
confidence: 99%